2020
DOI: 10.1371/journal.pone.0238413
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism or thrombosis in ARDS COVID-19 patients: A French monocenter retrospective study

Abstract: Hypercoagulability and endotheliopathy reported in patients with coronavirus disease 2019 (COVID-19) combined with strict and prolonged immobilization inherent to deep sedation and administration of neuromuscular blockers for Acute Respiratory Distress Syndrome (ARDS) may expose critically ill COVID-19 patients to an increased risk of venous thrombosis and pulmonary embolism (PE). We aimed to assess the rate and to describe the clinical features and the outcomes of ARDS COVID-19 patients diagnosed with PE duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 18 publications
2
44
1
Order By: Relevance
“…One major consequence is the high prevalence of deep vein thrombosis (DVT) demonstrated by studies performing duplex ultrasound examination of the lower limbs in patients hospitalized with severe pneumonia ( Zhang et al, 2020 ; Fraissé et al, 2020 ; Llitjos et al, 2020 ; Nahum et al, 2020 ; Ren et al, 2020 ; Voicu et al, 2020a ). The high prevalence of DVT exposes patients to a high risk of pulmonary embolism (PE) ( Contou et al, 2020 ; Poissy et al, 2020 ), especially when DVT is proximal, at the popliteal level, or above ( Konstantinides et al, 2020 ). DVT in COVID-19 patients may be responsible for approximately 10% of deaths in COVID-19 patients as shown by systematic autopsy findings ( Edler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One major consequence is the high prevalence of deep vein thrombosis (DVT) demonstrated by studies performing duplex ultrasound examination of the lower limbs in patients hospitalized with severe pneumonia ( Zhang et al, 2020 ; Fraissé et al, 2020 ; Llitjos et al, 2020 ; Nahum et al, 2020 ; Ren et al, 2020 ; Voicu et al, 2020a ). The high prevalence of DVT exposes patients to a high risk of pulmonary embolism (PE) ( Contou et al, 2020 ; Poissy et al, 2020 ), especially when DVT is proximal, at the popliteal level, or above ( Konstantinides et al, 2020 ). DVT in COVID-19 patients may be responsible for approximately 10% of deaths in COVID-19 patients as shown by systematic autopsy findings ( Edler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 104 included studies, mainly observational retrospective, 42 were reporting results from China (19-60), 19 from the U.S.A (61-79), 5 from the U.K (80-84), 24 across Europe, mainly Italy, Spain, France and the Netherlands (85-109), 10 from other countries (110-119) and 3 were international (120-122). All studies reported data on hospitalized patients due to COVID-19 and 35 of them included data for ICU nnnnnn(20, 25, 33, 36, 37, 41, 44, 45, 48, 52, 53, 56, 58, 66, 72, 73, 81-84, 86-89, 95, 96, 98, 101, 103, 106, 107, 109, 111, 119). Eight studies were pediatric (59, 60, 78, 79, 83, 84, 118, 119).…”
Section: Resultsmentioning
confidence: 99%
“…Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2) infection is characterized by fever and respiratory symptoms, 1 however, patients infected with SARS CoV-2 may present with a broad clinical spectrum, ranging from an asymptomatic disease to acute respiratory distress syndrome and multi-organ failure. Patients with COVID-19 infection have been reported to suffer from coagulation abnormalities consistent with infection-induced inflammatory changes, 2 4 in addition, Ackermann and colleagues 5 reported the presence of endothelial lesions, such as intercellular union disruption, disrupted cell membranes and cellular edema in the pulmonary endothelium during their post mortem study of 7 lungs obtained from patients who died from COVID-19. Not only do these patients often go through a hypercoagulability state but are also prone to suffer from prolonged immobilization; this leads critically ill patients to an increased risk of Venous Thromboembolism (VTE) and Pulmonary Embolism (PE).…”
Section: Introductionmentioning
confidence: 99%
“… 14 VTE has been associated with a poor prognosis and PE may be a turning point in these patients due to the increased hypoxemia and cardiac collapse. 2 , 3 , 10 We aimed to describe the clinical characteristics and outcomes of 26 COVID-19 patients diagnosed with PE during their hospital stay in a tertiary referral center for COVID-19 in Mexico City.…”
Section: Introductionmentioning
confidence: 99%